Plastic tension of porous plates due pure bending - H L, Levonyan; S V, Verlinski; A G, Tyagunov; D A, Tarasov (International Journal of Engineering and Technology, 2018)
The bending of the plate from rigid-plastic hardening material in the condition of plane deformation is investigated by analytical and numerical methods. Based on equations of the theory of plasticity of the porous materials the solution of the problem is lead to integration of the nonlinear differential equation regard to radial stress. The position of neutral axis is defined by numerical integration and the stress strain state components are received. Graphics of stress components and porosity changing are constructed on the height of the plate. The same problem simulated in ABAQUS software with the help finite element method. The results are compared.Â